2015
DOI: 10.1016/j.jpainsymman.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Buccal Tablet vs. Oral Morphine in Doses Proportional to the Basal Opioid Regimen for the Management of Breakthrough Cancer Pain: A Randomized, Crossover, Comparison Study

Abstract: When used in doses proportional to the basal opioid regimen, FBT showed a clear superiority and was well tolerated when compared with OM during the first 30 minutes, which is the approximate target for a timely intervention required for a BTcP medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
2
27
1
1
Order By: Relevance
“…This study has confirmed numerous observational trials showing the safety and effectiveness of doses proportional to the basal opioid regimen even in older patients or in patients receiving high doses of opioids [44,[54][55][56][57][58][59][60][61]. More recently, the effectiveness of FBT and oral morphine was compared by using similar doses, proportional to the basal opioid regimen [62], providing an advantage of FBT that was more representative in comparison with previous comparative studies in which the dose of FBT was titrated [37,40]. It is of interest that in a real-world study reflecting clinical practice, the titration process provided doses even higher than those expected by using doses proportional to basal opioid regimen [63].…”
Section: Ninth Commandment: Dosing Btcp Medicationssupporting
confidence: 79%
“…This study has confirmed numerous observational trials showing the safety and effectiveness of doses proportional to the basal opioid regimen even in older patients or in patients receiving high doses of opioids [44,[54][55][56][57][58][59][60][61]. More recently, the effectiveness of FBT and oral morphine was compared by using similar doses, proportional to the basal opioid regimen [62], providing an advantage of FBT that was more representative in comparison with previous comparative studies in which the dose of FBT was titrated [37,40]. It is of interest that in a real-world study reflecting clinical practice, the titration process provided doses even higher than those expected by using doses proportional to basal opioid regimen [63].…”
Section: Ninth Commandment: Dosing Btcp Medicationssupporting
confidence: 79%
“…5,6) Besides, its analgesic action, morphine has anti-nociceptive effect, and might even change tumor progression. In our earlier study, we found that opioid molecule fentanyl could inhibit the vitality of gastric carcinoma cells and cell cycle progression, the mechanism of which might be associated with inhibition of nuclear factor-kappaB (NF-κB) nuclear translocation and phosphatase and tensin homolog deleted from chromosome 10 (PTEN) tumor suppressor gene upregulation.…”
mentioning
confidence: 99%
“…Studies with other fentanyl transmucosal formulations are consistent with this result, suggesting that choosing the initial dose of a BTCP opioid based on the current ATC dose is not supported by the published data [30,31]. However, there has been a study suggesting doses of a transmucosal immediate-release buccal fentanyl formulation proportional to a patient's ATC opioid regimen was more efficacious than oral morphine during the first 30 min posttreatment [32]. Another approach calculated the dose of a transmucosal immediate-release sublingual fentanyl formulation for BTCP from a precalculated morphine dose for BTCP and found that a conversion ratio of 1/50 provided efficacious analgesia [33].…”
Section: Discussionmentioning
confidence: 86%